Biomimetic nanovesicles for targeted delivery of doxorubicin and erlotinib to lung cancer cells - Sterman, Raquel González (2024)
Lung cancer remains a leading cause of cancer-related mortality, and current therapies often suffer from limited specificity and adverse effects, calling for the development of more effective and targeted treatment strategies. In this study, we developed and characterized biomimetic nanovesicles (NVs) derived from A549 lung cancer cells, designed to co-deliver doxorubicin (DOX) and erlotinib (ERL) for enhanced targeting of lung cancer cells, thereby minimizing off-target toxicity. The sizes of both blank and drug-loaded NVs, measured by Nanoparticle Tracking Analysis, were 163 ± 9 nm and 187 ± 17 nm, respectively. Additionally, morphological analysis showed the NVs as spherical structures, with sizes within the range of 100 - 200 nm, indicating an adequate size range for cellular uptake. The zeta potential and polydispersity index were measured at -10 ± 3 mV and 0.24 ± 0.04 for empty NVs, and -18 ± 4 mV and 0.57 ± 0.02 for loaded NVs, indicating successful drug encapsulation. Spectroscopy techniques of Fourier Transform Infrared and Micro-Raman confirmed the presence of both DOX and ERL within the NVs. Encapsulation efficiencies were 40 ± 2% for DOX and 93 ± 1% for ERL, measured via a novel high-performance liquid chromatography method that was developed and validated for simultaneous quantification of DOX and ERL. Release studies demonstrated that 60% of DOX and 85% of ERL were released from the nanovesicles after 72h, with no significant difference at pH 7.4 and 6.8. Cellular uptake studies using confocal fluorescence microscopy and flow cytometry showed preferential internalization of NVs by A549 cancer cells compared to MRC-5 non-cancerous cells, showing the potential of NVs to interact with homologous cells. Furthermore, cell viability assays indicated higher viability in MRC-5 cells treated with NVs compared to A549 cells, suggesting the nanosystem\'s potential to selectively target cancer cells while sparing non-cancerous tissues. Clonogenic assays corroborated these findings, showing long-term survival of MRC-5 cells and a significant reduction in A549 cell survival following NV treatment. These results highlight the potential of this biomimetic nanosystem as a promising delivery platform for lung cancer therapy, offering targeted treatment with reduced off-target effects and long-term therapeutic efficacy.